Influence of age and practices on rubber and nutrient management of intercrop on bird’s eye chilli under agroforestry system - Kannur, Siddappa; Patil, S.J.; Inamati, S.S. (Indian Journal of Agroforestry, 2022)
A field experiment on influence of age and practices on rubber and nutrient management of intercrop on yield and quality parameters of bird’s eye chilli (BEC) under agroforestry system was conducted at farmer’s field during two successive years (2017 to 2019). The results showed that age of rubber plantation and practices followed on rubber had significant influence on number of fruits per plant per picking, fresh weight and dry weight of 100 fruits, capsaicin content and oleoresin content of BEC. The BEC plants treated with combined application of FYM, Azotobacter and PSB registered highest yield and quality parameters of BEC as compared to the rest of the treatments. Interactions were significant for few of the yield and quality parameters. Thus, combined use of FYM, Azotobacter and PSB on BEC under organic practice on rubber at two-year-old rubber plantation proved better in improving the yield and quality parameters of BEC under agroforestry system